MAPPING OF RELIGIOUS CENTERS OF AFRICAN ORIGIN IN THE METROPOLITAN REGION OF THE STATE OF RIO DE JANEIRO - Rego, Luiz Felipe Guanaes; Russo, Gustavo Martins; Tinoco, Elaine; Lamar, Hanna (Revista Brasileira de Cartografia, 2014)
Despite the enormous African legacy in Brazilian society, the traditional centers of African religion are not recognized by Brazilian legislation as are other predominant religions within the country, thereby ignoring the social function of such centers as well as depriving such institutions of the benefits of recognition under the Constitution. Furthermore, these African religious centers had historically suffered formal persecution from the State. Today, such centers of African religion continue to suffer prejudice and persecution from certain Protestant Christian religions. In an effort to give support to the role such centers play in their respective communities, a geographical survey was conducted to reveal their prevalence. This article evaluates the thematic maps produced by the Project for the Mapping of Religious Centers of African Origin in the Metropolitan Region of the State of Rio de Janeiro, developed by the departments of Geography, Social Services and Social Sciences at the Pontifical University of Rio de Janeiro (PUC-RIO) in partnership with Brazil’s Special Secretariat of Policies for the Promotion of Racial Equality. The maps, which present information derived from surveys conducted at over 800 religious centers of African origin, were studied in terms of the geographical areas used as research evaluation units and in terms of representation techniques and mapped variables. The maps were shown to be very efficient in locating these religious centers and in presenting the social responsibility actions developed in their communities. The maps and research demonstrate the current prejudice suffered by centers of African religion, where half of those surveyed confirmed the incidence of intolerance to African religion.